(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the influence of contemporary materialistic and secular worldviews on human faith and spiritual consciousness. The study examines modern forms of materialism, including scientism, moral relativism, secularism, and consumer culture, as well as their theological and ethical consequences. Furthermore, the historical formation of kalam theology, its defensive role in protecting Islamic creed, and its methodological foundations based on the harmony of reason and revelation are discussed. Special attention is given to the Maturidi school and its methodological relevance in addressing contemporary ideological and theological challenges. The article concludes that kalam theology remains an essential methodological system for strengthening theological stability and ideological immunity in modern Muslim societies.